Underwater noise levels in the Strait of Gibraltar and surrounding waters: findings from the AMIGOS survey - Perez Tadeo, Maria; O’Brien, Joanne (Frontiers in Marine Science, 2025)
Snapshots of underwater sound were collected during a multidisciplinary research survey at 14 stations south of the Iberian Peninsula, including the Strait of Gibraltar, an area characterized by intense maritime traffic. Sound Pressure Levels (SPLs) were quantified at each station using 1/3-octave bands, with a focus on the 63 Hz and 125 Hz centered frequency bands, as recommended by the Marine Strategy Framework Directive (MSFD). When possible, the main noise sources were also identified. SPLs in the 63 Hz band ranged from 104.91 to 132.24 dB re 1 μPa, with an average of 113.21 dB re 1 μPa. In the 125 Hz band, SPLs ranged from 104.31 to 129.82 dB re 1 μPa, with an average of 110.27 dB re 1 μPa. The highest SPLs were recorded at the stations in the Strait of Gibraltar and the Alboran Sea. A methodology consisting of attaching a SoundTrap to the research vessel’s CTD rosette was tested and proved to be an effective approach for assessing the underwater soundscape from vessels of opportunity.